A refined two-step oligoribonucleotide interference-PCR method for precise discrimination of nucleotide differences. Issue 1 (December 2018) - Fujita, Toshitsugu; Yuno, Miyuki; Kitaura, Fusako; Fujii, Hodaka
Abstract We previously developed oligoribonucleotide (ORN) interference-PCR (ORNi-PCR), in which an ORN hybridises with a complementary DNA sequence and inhibits PCR amplification across the sequence in a sequence-specific manner. Suppression of target amplification by ORNi-PCR can be used to detect nucleotide differences such as mutations in a target sequence. In the present study, we refined the ORNi-PCR method and established a detailed technical protocol to precisely discriminate single-nucleotide differences. We first revealed that a two-step (denaturing and annealing plus elongation) rather than a standard three-step (denaturing, annealing and elongation) method is more suitable for stably hybridising an ORN to its target DNA sequence for sequence-specific suppression of target amplification. We then optimised the ORNi-PCR method using two-step cycles and established a step-by-step technical protocol. The optimised Two-Step ORNi-PCR method could discriminate single-nucleotide differences in genomic DNA or cDNA introduced by genome editing or mutations in cancer cells. In addition, we showed that Two-Step ORNi-PCR can detect the cancer cells possessing a single nucleotide mutation in a target locus mixed with a large number of cells harboring wild-type sequences in the locus so that the number of the cancer cells is only 0.2% of the total cell number. Two-Step ORNi-PCR is useful for simple, precise, cost-effective and positive detection of nucleotide differences in a wide range of molecular biology and medical applications.